2013
DOI: 10.3109/0886022x.2013.777890
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonsurgical Periodontal Treatment on C-Reactive Protein Levels in Maintenance Hemodialysis Patients

Abstract: Objective: C-reactive protein (CRP) has been implicated as a possible mediator of the association between periodontitis and several systemic diseases. This study evaluated the impact of nonsurgical periodontal treatment on the serum levels of CRP in chronic kidney disease (CKD) patients on hemodialysis. Methods: A total of 77 CKD patients on hemodialysis were included in this study. At baseline, periodontal examination was assessed for all the patients, and chronic periodontitis was defined through clinical at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…In addition, the same study found no significant difference in serum CRP levels ( p = 0.23) between HD patients with no/mild periodontitis ( n = 100) and moderate/severe periodontitis ( n = 68). This non-significant relationship between serum CRP levels and severity of periodontal disease was supported by other investigators [10,12]. Moreover, salivary CRP levels in HD patients were reported to be significantly higher compared to both controls and patients with CKD not receiving HD [34].…”
Section: Hemodialysissupporting
confidence: 64%
See 2 more Smart Citations
“…In addition, the same study found no significant difference in serum CRP levels ( p = 0.23) between HD patients with no/mild periodontitis ( n = 100) and moderate/severe periodontitis ( n = 68). This non-significant relationship between serum CRP levels and severity of periodontal disease was supported by other investigators [10,12]. Moreover, salivary CRP levels in HD patients were reported to be significantly higher compared to both controls and patients with CKD not receiving HD [34].…”
Section: Hemodialysissupporting
confidence: 64%
“…For example, one report showed that serum CRP levels were significantly decreased ( p = 0.001) after periodontal treatment in 41 patients receiving HD [30]. Similar results have also been reported in 77 HD patients treated with non-surgical methods [12]. In contrast, other investigators have reported that serum CRP levels in HD patients with treated chronic periodontitis ( n = 43) were similar ( p = 0.634) to untreated patients ( n = 30) [37].…”
Section: Hemodialysissupporting
confidence: 57%
See 1 more Smart Citation
“…Based on the biological evidence that host defense cells release immunoinflammatory mediators such as IL-6, TNFα, MMPs, and PGE2, and stimulate the production of acute phase proteins such as PCR and hepcidin, in response to periodontal disease, the results of our study are similar to the findings of previous studies. 23,24,25,26 There was a significant reduction in IL-6 and CRP in both groups (with and without periodontal disease), demonstrating that immunoinflammatory mediators and acute phase proteins decrease after inflammation and infection. The hepatic peptide hormone hepcidin regulates the absorption of iron from the diet; plasma iron concentrations and the distribution of iron in the tissues and its increase are linked to the inflammatory and infectious response, leading to a reduction in iron availability.…”
Section: Discussionmentioning
confidence: 91%
“…[1112] Concluding remarks of the other studies that the periodontal treatment downturns the elevated CRP levels. [13]…”
Section: Discussionmentioning
confidence: 99%